(untitled) (Research, Society and Development, 2023)
A Quality Management System is the part of the management system that focuses on achieving quality-related results. The ISO 9001 series quality management system standard accredits the ability of organizations to offer products or services that meet customer requirements and applicable regulations. The objective of this work was to collect information about the implementation of ISO 9001 standards in Ecuadorian dental clinics. A review of the available literature was carried out, using the PubMed, Google Scholar, and Scielo databases, including studies in English and Spanish reported from 2018 to 2022; Those repeated studies that were found within the search engines and non-competent studies to our analysis were excluded. The results showed a positive overview of the application of ISO standards in organizations from different areas, however, there are cases in which, despite having ISO 9001 certification, when measuring quality with respect to defects found in the process and procedures , they did not present quality of world competition, with which they recommend implementing more techniques which help to improve the organization processes within the companies. It was concluded that the implementation of ISO Standards by the different organizations improves collaborative work among staff, minimizes errors, mitigates risks and allows anticipation of the needs of their clients.